Effectiveness of interventions for reducing non-occupational sedentary behaviour in adults and older adults: a systematic review and meta-analysis. Issue 19 (October 2019) - Shrestha, Nipun; Grgic, Jozo; Wiesner, Glen; Parker, Alexandra; Podnar, Hrvoje; Bennie, Jason A; Biddle, Stuart J H; Pedisic, Zeljko
Abstract : Background: No systematic reviews of the effectiveness of interventions for reducing non-occupational sedentary behaviour are available. Therefore, the aim of this systematic review was to assess the effectiveness of interventions for reducing non-occupational sedentary behaviour in adults and older adults. Methods: An electronic search of nine databases was performed. Randomised controlled trials (RCT) and cluster RCTs among adults testing the effectiveness of interventions aimed to reduce non-occupational sedentary behaviour were considered for inclusion. Two review authors independently screened studies for eligibility, completed data extraction and assessed the risk of bias. Results: Nineteen studies that evaluated multicomponent lifestyle interventions, counselling or education, television (TV) control devices and workplace interventions were included. Evidence from the meta-analyses suggested that interventions can reduce leisure sitting time in adults in the medium term (−30 min/day; 95% CI −58 to –2), and TV viewing in the short term (−61 min/day; 95% CI −79 to –43) and medium term (−11 min/day; 95% CI −20 to –2). No significant pooled effects were found for transport sitting time, leisure-time computer use and longer term outcomes. No evidence was available on the effectiveness of interventions for reducing non-occupational sedentary time in older adults. Conclusions: The findings of this systematic review suggest the interventions may be effective in reducing non-occupational sedentary behaviour in the short to medium term in adults. However, no significant effect was found on longer term outcomes. The quality of evidence was, however, low to very low. No evidence was available on the effectiveness of non-occupational interventions on reducing sedentary time in older adults. Further high-quality research with larger samples is warranted.